2012
DOI: 10.1038/nature11451
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dendritic processing determines angular tuning of barrel cortex neurons in vivo

Abstract: Layer 4 neurons in primary sensory cortices receive direct sensory information from the external world. A general feature of these neurons is their selectivity to specific features of the sensory stimulation. Various theories try to explain the manner in which these neurons are driven by their incoming sensory information. In all of these theories neurons are regarded as simple elements summing small biased inputs to create tuned output through the axosomatic amplification mechanism. However, the possible role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
274
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(301 citation statements)
references
References 29 publications
18
274
1
3
Order By: Relevance
“…Firstly, we predict that hyperpolarization not only broadens somatic tuning (Jia et al, 2010;Lavzin et al, 2012) but it also sharpens dendritic tuning (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we predict that hyperpolarization not only broadens somatic tuning (Jia et al, 2010;Lavzin et al, 2012) but it also sharpens dendritic tuning (Fig. 6).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the spike timing dependence of the Ca 2+ transient amplitudes showed a supralinearity when the synaptic stimulus preceded the back-propagating action potential (bAP) and a sublinearity when the order was reversed. Recently, a study combining wholecell recordings in vivo and two-photon imaging in vitro investigated the cellular mechanisms of angular tuning in L4 neurons in the mouse barrel cortex (11). The results indicated that angular tuning of somatic voltage responses involves a complex nonlinear dendritic interplay of thalamo-cortical and cortico-cortical inputs.…”
mentioning
confidence: 99%
“…synaptic integration | 2-layer model | active dendrites | NMDA spike | dendritic spike O n the path to understanding the diverse information processing functions of the brain, it is essential to develop simplified models of individual neurons. The classical view that a neuron collects excitatory and inhibitory influences from across its dendritic arbor and passively funnels them to a single spikegenerating zone near the soma has been challenged by the finding that dendrites generate local spikes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and can support a variety of compartmentalized computations (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). We previously showed that the input-output (i/o) behavior of a dendritic subtree, whose branches emanate from a main trunk or soma, can be described by a two-layer model (2LM), where the first layer consists of multiple independent dendritic "subunits" with stereotyped nonlinear i/o functions.…”
mentioning
confidence: 99%